2011
DOI: 10.1089/mdr.2010.0199
|View full text |Cite
|
Sign up to set email alerts
|

ClinicalNeisseria gonorrhoeaeIsolates in the United States with Resistance to Azithromycin Possess Mutations in All 23S rRNA Alleles and themtrRCoding Region

Abstract: We identified strains of Neisseria gonorrhoeae in San Diego County, California, that possess high levels of resistance to azithromycin (8.0-16.0 μg/ml MIC). These isolates contain a combination of mutations in both the 23S rRNA loci and mtrR genes. This is the first description of such isolates in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…In the current study, only seven AZM-R isolates contained mutation C2611T, whereas the remaining large number of AZM-R isolates contained four wild-type alleles. These findings contrast, however, with other reports from Canada [ 9 ], the United States [ 11 , 20 ] and the United Kingdom [ 10 ], which most of the AZM-MLR isolates contained this mutation was more than 80 %. Notably, all the above-mentioned seven AZM-R isolates that contained the mutation C2611T showed reduced susceptibility to ceftriaxone.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In the current study, only seven AZM-R isolates contained mutation C2611T, whereas the remaining large number of AZM-R isolates contained four wild-type alleles. These findings contrast, however, with other reports from Canada [ 9 ], the United States [ 11 , 20 ] and the United Kingdom [ 10 ], which most of the AZM-MLR isolates contained this mutation was more than 80 %. Notably, all the above-mentioned seven AZM-R isolates that contained the mutation C2611T showed reduced susceptibility to ceftriaxone.…”
Section: Discussioncontrasting
confidence: 98%
“…Mutations at various genes such as 23S rRNA, mtrR and penA (encoding penicillin-binding protein 2, PBP2), have been identified associating with chromosomally mediated resistance to AZM [ 10 , 11 ] and ESCs [ 12 ] in N. gonorrhoeae . Globally, AZM-R together decreased susceptibility to ESCs in N. gonorrhoeae has only rarely been reported [ 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the past 8 decades, gonorrhea has been treated successfully with antibiotics, despite patterns of resistance, but over the last several years, multidrug-resistant and untreatable strains have begun to emerge worldwide. Resistant strains include isolates from both Eastern and Western Europe ( 3 , 4 ), Asia ( 5 7 ), and recently the United States ( 8 10 ). This rise in antibiotic-resistant strains may be linked, in part, to an increase in availability of over-the-counter antibiotics, particularly in many parts of Asia.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study investigating isolates from San Diego County with unusually a high MIC for azithromycin (MIC of 8.0-16.0) showed that those isolates were found to have the NG-MAST type ST2992. 20 In this study, ST2992 isolates were found to have azithromycin MIC ranging from 0.03 to 1.0 (nonalert value). Possibly, the loci …”
Section: Discussionmentioning
confidence: 69%